2019
DOI: 10.18662/rrem/124
|View full text |Cite
|
Sign up to set email alerts
|

Study of Aspects Facilitating «Lifelong Learning» Competence Development in High School Students

Abstract: The “lifelong learning” competence is considered in the article as an integrated ability of an individual, incorporating knowledge, skills and habits  that students acquire during schooling, as well as certain qualities that ensure their readiness for further learning, socialization and personal growth. Success-oriented motivation and success in learning are determined as the essential prerequisites for the “lifelong learning” competence development in high school learners. The article presents the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Similarly, Güzel (2017) also reported that students' lifelong learning levels were at moderate levels. Matvieieva et al (2019) found that the lifelong learning levels of secondary school students were at a moderate level. Also, Pesen and Epçeçen (2017) stated that the lifelong learning levels of secondary school students were at moderate levels.…”
Section: Discussion Regarding the First Research Questionmentioning
confidence: 96%
“…Similarly, Güzel (2017) also reported that students' lifelong learning levels were at moderate levels. Matvieieva et al (2019) found that the lifelong learning levels of secondary school students were at a moderate level. Also, Pesen and Epçeçen (2017) stated that the lifelong learning levels of secondary school students were at moderate levels.…”
Section: Discussion Regarding the First Research Questionmentioning
confidence: 96%
“…Generalization of the researches (Prontenko, et al, 2019;Zhukevych, et al, 2019) and conclusions of a number of scientists (Barko et al, 2020a;Ball, 2014;Kubaienko et al, 2021;Matvieieva et al, 2019;Raven, 2002); allows to make systematic descriptions of the future law enforcement officers' self-educational competence formedness.…”
Section: Limits and Discussionmentioning
confidence: 99%
“…At the same time, the problem of formation and development of self-educational skills and abilities i. e. components of selfeducational competence has repeatedly attracted attention of scientists. The works by Ball (2014), Matvieieva, Ovcharenko, Korchagina, Kuznetsova, & Grineva (2019), Torkos & Egerau (2020) and others are of great importance for methodological understanding of the aforementioned issue; they identify the features of self-education as a purposeful independent human activities in choosing topics, time and means of work to obtain knowledge and substantiate the optimal methods of organizing self-education. Study of the problem of self-education and self-educational competence within the system of professional training is an important area of research at present.…”
Section: Introductionmentioning
confidence: 99%
“…At this age, the system of value orientations becomes conscious and sustainable. There is little research into the value and sense sphere of future educators (Halian et al, 2020a;Ivanchuk et al, 2020;Kalenchuk, 2019;Matvieieva et al, 2019;Miliaieva, 2013). The values of young people (in general) were studied (Leontyev, 2003).…”
Section: Discussionmentioning
confidence: 99%